Keynesian, Classical and New Keynesian Approaches to Fiscal Policy: Comparison and Critique - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2012)
The short-run macroeconomic effectiveness of fiscal policy depends on the effect of policy on AD and the effect of AD on output. This paper examines how macroeconomic perspectives (Keynesian, Post Keynesian, monetarist, classical, new classical, and new Keynesian) describe the effect of AD on output, thereby making or denying space for fiscal policy to impact output. The neo-Ricardian hypothesis (NRH) concerns the effect of bond financed deficits on AD. The NRH turns on the microeconomic behavior of households and can therefore hold in principle in both classical and Keynesian models. Recent new Keynesian arguments about fiscal policy being effective at the zero lower bound represent another capital market imperfection critique of the NRH.
urn:nbn:de:101:1-201211143605
Keywords: E6; E62; H3; 330; Fiscal policy; Keynesian; Post Keynesian; monetarist; classical; new Keynesian; neo-Ricardian hypothesis; zero lower bound; Finanzpolitik; Wirkungsanalyse; Dogmengeschichte; Vergleich; Theorie